Albumin-Based Nanocarriers for the Simultaneous Delivery of Antioxidant Gene and Phytochemical to Combat Oxidative Stress - Naqvi, Saba; Khanadeev, Vitaly A.; Khlebtsov, Boris N.; Khlebtsov, Nikolai G.; Deore, Monika S; Packirisamy, Gopinath (Frontiers in Cell and Developmental Biology, 2022)
Human serum albumin (HSA) nanoparticles are promising biocompatible, non-toxic and non-immunogenic platforms for biomedical applications such as bioimaging, drug and gene delivery. The development of non-viral gene delivery vectors is a great challenge for efficient and safe gene therapy. Sulforaphane(SF) can stimulate the expression of antioxidant genes via activation of a nuclear transcription factor, the erythroid-2 related factor 2 (Nrf-2). Here, we use polyethyleneimine (PEI) stabilized HSA nanoparticles to stimulate endogenous antioxidant defence mechanisms in lung epithelial cells L-132 through the combinatorial effect of SF drug and antioxidant superoxide dismutase 1 gene (pSOD1 plasmid) delivered by HSA-PEI-SF-pSOD1 nanocomposites (NCs). The developed NCs demonstrated high biocompatibility (L-132 viability, >95%, MTT assay) and high antioxidant activity because of efficient entry in L-132 cells and delivery of encoding SOD1 gene and SF at a very low (3µg) dose. A high transfection efficiency of L-132 cells ( 66%, fluorescent microscopy) was obtained with the GFP tagged transgene SOD1-GFP. We speculate that the antioxidant activity of HSA-PEI-SF-pSOD1 NCs in L-132 cells is due to the initial release of SF followed by subsequent SOD1 gene expression after three to four days of incubation. Hence, the developed HSA-based NCs can be efficient biocompatible nanocarriers for safe and effective drug and gene delivery applications to treat disease with high oxidative stress due to combinatorial SF and SOD1 gene mechanisms.